Problems of preserving regional biodiversity under climate change: Threats and opportunities - Bezrukova Tatiana; Treyman Marina; Kuvshinova Oksana (BIO Web of Conferences)
Biodiversity, a phrase describing the variety of living organisms on the planet, is a source of vital resources and services for humanity. However, human influences on ecosystems are causing rapid and widespread loss of biodiversity. Humans are currently transforming the environment at a faster rate and over vast areas than ever before. In addition, climate change is placing additional stress on natural ecosystems. Life on Earth has always had to adapt to climate change, which has contributed significantly to the evolutionary processes that led to the emergence of modern plant and animal species. This article provides a comparative review of alternative research methods and describes principles for collecting and analyzing high-quality information. This paper proposes to use simulation modeling and statistical analysis to study and assess environmental and economic indicators, which will allow us to draw a conclusion about possible significant transformations not only of the climate, but also of biodiversity. Of course, in order to reduce the negative consequences of these changes, it is critically important to take preventive steps to adapt to new climatic conditions and preserve the biodiversity of the region.